The Impact of Dabigatran Treatment on Sinusoidal Protection Against Hepatic Ischemia/Reperfusion Injury in Mice. Issue 3 (9th December 2020) - Noguchi, Daisuke; Kuriyama, Naohisa; Hibi, Taemi; Maeda, Koki; Shinkai, Toru; Gyoten, Kazuyuki; Hayasaki, Aoi; Fujii, Takehiro; Iizawa, Yusuke; Tanemura, Akihiro; Murata, Yasuhiro; Kishiwada, Masashi; et al.
Abstract : Thrombin is a key player in the coagulation cascade, and it is attracting much attention as a promotor of cellular injured signaling. In ischemia/reperfusion injury (IRI), which is a severe complication of liver transplantation, thrombin may also promote tissue damage. The aim of this study is to reveal whether dabigatran, a direct thrombin inhibitor, can attenuate hepatic IRI with focusing on a protection of sinusoidal endothelial cells (SECs). Both clinical patients who underwent hepatectomy and in vivo mice model of 60‐minute hepatic partial‐warm IRII, thrombin generation was evaluated before and after IRI. In next study, IRI mice were treated with or without dabigatran. In addition, hepatic SECs and hepatocytes pretreated with or without dabigatran were incubated in hypoxia/reoxygenation (H‐R) environment in vitro. Thrombin generation evaluated by thrombin–antithrombin complex (TAT) was significantly enhanced after IRI in the clinical study and in vivo study. Thrombin exacerbated lactate dehydrogenase cytotoxicity levels in a dose‐dependent manner in vitro. In an IRI model of mice, dabigatran treatment significantly improved liver histological damage, induced sinusoidal protection, and provided both antiapoptotic and anti‐inflammatory effects. Furthermore, dabigatran not only enhanced endogenous thrombomodulin (TM) but also reduced excessive serum high‐mobility group box‐1 (HMGB‐1). In H‐R models of SECs, not hepatocytes, pretreatment with dabigatran markedly attenuated H‐R damage, enhanced TM expression in cell lysate, and decreased extracellular HMGB‐1. The supernatant of SECs pretreated with dabigatran protected hepatocytes from H‐R damage and cellular death. Thrombin exacerbated hepatic IRI, and excessive extracellular HMGB‐1 caused severe inflammation‐induced and apoptosis‐induced liver damage. In this situation, dabigatran treatment improved vascular integrity via sinusoidal protection and degraded HMGB‐1 by endogenous TM enhancement on SECs, greatly ameliorating hepatic IRI.